The robust software metric data model defined in XML. - Ng , Keng Yap; Abdul Ghani, Abdul Azim; Mamat, Ali; Zulzalil, Hazura (IJCSNS (International Journal of Computer Science and Network Security), 2008)
Software metric data model has always been restructured, redefined to fit their respective software metrics, and yet it will never been permanently shaped. It is important to have a generic data model to handle software measurement data in digital format that can actually help making software metrics definition in future much robust, definable and structured. In this paper software metric data model is defined in eXtensible Markup Language (XML) with three main characteristics: portability, extensibility and also reusability. The newly defined software metric data model is SMML. SMML has been tested via proof of concepts through build and evaluate methodology. A testing toolkit and an Application Programming Interface (API) were produced in helping the evaluation of SMML viability. The model has been tested robust with its portability, extensibility and reusability.